2011
DOI: 10.1186/1471-2172-12-29
|View full text |Cite
|
Sign up to set email alerts
|

Production of antibodies with peptide-CpG-DNA-liposome complex without carriers

Abstract: BackgroundThe screening of peptide-based epitopes has been studied extensively for the purpose of developing therapeutic antibodies and prophylactic vaccines that can be potentially useful for treating cancer and infectious diseases such as influenza virus, malaria, hepatitis B, and HIV. To improve the efficacy of antibody production by epitope-based immunization, researchers evaluated liposomes as a means of delivering vaccines; they also formulated adjuvants such as flagella and CpG-DNA to enhance the magnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(104 citation statements)
references
References 43 publications
2
101
1
Order By: Relevance
“…The PO-ODN, specifically MB-ODN 4531(O) containing immunomodulatory CpG motifs, regulates expression of Th1 cytokines and does not have severe side effects. We also found that the PO-ODN encapsulated in a phosphatidyl-β-oleoyl-γ-palmitoyl ethanolamine (DOPE): cholesterol hemisuccinate (CHEMS) complex (Lipoplex(O)) is able to enhance the stimulation of immune responses in the cells of humans and mice (15). Here, we investigated the effects of liposome-encapsulated PO-ODN or PS-ODN on TLR9-mediated signal transduction pathways and performed screening of B cell epitopes using several peptides and Lipoplex(O).…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…The PO-ODN, specifically MB-ODN 4531(O) containing immunomodulatory CpG motifs, regulates expression of Th1 cytokines and does not have severe side effects. We also found that the PO-ODN encapsulated in a phosphatidyl-β-oleoyl-γ-palmitoyl ethanolamine (DOPE): cholesterol hemisuccinate (CHEMS) complex (Lipoplex(O)) is able to enhance the stimulation of immune responses in the cells of humans and mice (15). Here, we investigated the effects of liposome-encapsulated PO-ODN or PS-ODN on TLR9-mediated signal transduction pathways and performed screening of B cell epitopes using several peptides and Lipoplex(O).…”
Section: Introductionmentioning
confidence: 97%
“…We refer to MB-ODN 4531(O) encapsulated in a DOPE : CHEMS) complex as Lipoplex(O). Lipoplex(O) induced the production of cytokines such as IL-6, IL-12, and IFN-γ in mouse splenocytes and hPBMCs, and also induced secretion of IL-12 and IFN-γ for much longer time periods than MB-ODN 4531(O) did by in vivo application, in a TLR9-dependent manner (15). In this study, we determined the effects of liposome-encapsulated MB-ODN 4531(S) (PS-ODN) on IL-8 promoter activity in a human B cell line (RPMI 8226) and the mouse macrophage cell line, RAW 264.7.…”
Section: Effect Of Ps-odn Encapsulated In Liposomes On Il-8 Promoter mentioning
confidence: 99%
See 3 more Smart Citations